PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) DENGAN GENDER DIVERSITY SEBAGAI VARIABEL MODERASI - I Wayan Kartana; Diah kurniawati; I G. A Intan Saputra Rini; Ida Ayu Sri Meitri (Faculty of Economics and Business, Universitas Warmadewa, 2025)
This study aims to provide empirical evidence regarding the impact of Profitability, Leverage, and Firm Size on Corporate Social Responsibility (CSR), with Gender Diversity acting as a moderating variable in companies operating in the mining sector and listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. By collecting samples that meet the predetermined criteria, a sample of 20 companies was obtained for this period. The analytical techniques used in this study include classical assumption tests, multiple linear regression, coefficient of determination analysis, moderating regression analysis, and hypothesis testing using t-tests. The findings indicate that Profitability and Firm Size have a positive impact on CSR disclosure, while Leverage shows a negative impact on CSR disclosure. Additionally, Gender Diversity has been shown to moderate the relationship between Profitability, Leverage, and Firm Size on CSR disclosure in mining companies listed on the Indonesia Stock Exchange during the period of 2019-2023. Keywords: Profitability, Leverage, Company Size, and Corporate Social Responsibility (CSR) Disclosure